2018
DOI: 10.1177/2292550318800321
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Plastic Surgeons When Selecting New Colleagues

Abstract: Introduction: As plastic surgeons are continuing to form larger groups, it is essential to select candidates who will contribute to a positive work environment. This article shows which traits may be the most valuable when selecting candidates and in which ways a selection committee may want to focus their search. Methods: For the study, the Canadian Society of Plastic Surgeons' members answered a survey containing questions about demographics, the factors which influence the selection process, and their hirin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 18 publications
2
18
1
Order By: Relevance
“… 12 More than two-thirds of the directors look for familiar aspiring residents, hence they prefer candidates who took electives/rotations at their institution. 8 Contrary to common belief, most of the program directors in our cohort look for applicants with background knowledge in plastic surgery; this can be achieved especially in rotations and electives. Notwithstanding, it is a challenging step as most of the curricula in Saudi universities overlook plastic-surgery–related topics.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“… 12 More than two-thirds of the directors look for familiar aspiring residents, hence they prefer candidates who took electives/rotations at their institution. 8 Contrary to common belief, most of the program directors in our cohort look for applicants with background knowledge in plastic surgery; this can be achieved especially in rotations and electives. Notwithstanding, it is a challenging step as most of the curricula in Saudi universities overlook plastic-surgery–related topics.…”
Section: Discussionmentioning
confidence: 95%
“… 3 Oxley and Lotto regarded properly answering questions in the interview and making a good impression as the most important factor when selecting residents. 8 On the other hand, a review of literature revealed that only 11 of 34 studies have found a positive correlation between interviews and performance during residency, in terms of clinical evaluations, in-training examinations, licensing board examinations, and a composite score or rank of residents’ performance. This disparity between interview expectations and future performance can be explained, in part, by lack of structure, inevitable subjectivity, and interpersonal and social skills.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations